The nature of the NEET youth segment, its features and parameters in both domestic and global conditions - Khusainova, Zh.S.; Zhartay, Zh.M.; Abauova, G.M.; Lambekova, A.N.; Syzdykova, D.I. (KU Publ., 2021)
Object: Identification of the nature, features, parameters, and socio-economic causes of the NEET youth phenomenon in both world and domestic conditions. Methods: Methods of system, structural-functional, comparative, statistical analysis. Results: The nature of NEET youth, latent causes, and systemic factors of its genesis and development are revealed; a categorical apparatus of the socio-economic space of NEET youth is specified; the NEET youth segment and its parameters in both world and domestic conditions are structured. Conclusions: If ignored, both phenomenon and current state of NEET youth may lead to stale and stable, stagnant unemployment in the future, which further aggravates both social and macroeconomic issues. Since today the NEET youth segment is increasing, it is necessary to develop a comprehensive model of its reduction based on convergence of three components: productive employment (to form the motivation of NEET youth to work); post-industrial education (to acquire professional skills in information environment and globalizing context of their appliance); and inclusive development (as a constant of modern socialization of the economy.)
NEET-жастар сегментінің табиғаты, оның отандық жəне əлемдік жағдайдағы ерекшеліктері мен параметрлері
Природа сегмента NEET-молодежи, ее особенности и параметры в отечественных и мировых условиях
Keywords: youth; NEET youth; youth unemployment; productive employment